2013
DOI: 10.1111/tbed.12051
|View full text |Cite
|
Sign up to set email alerts
|

Proper Quality Control of Formulated Foot-and-Mouth Disease Vaccines in Countries with Prophylactic Vaccination is Necessary

Abstract: Vaccination is considered as an important tool to control foot-and-mouth disease (FMD). A good quality vaccine containing relevant serotypes and matching strains is a pre-requisite for vaccination to be effective. The present study investigated the quality of different brands of FMD vaccine available in Pakistan, including three locally produced and two imported products. All the vaccines were found free of bacterial or fungal contamination. No adverse effects were noted in suckling mice and buffalo calves ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…This was also observed in our findings that animals were vaccinated three months ago. This finding was also coincides with Jamal et al, (2013) who reported very low humoral immune responses against FMDV by the locally produced vaccines. The failure of vaccination may be due to differences between the circulating field strains and the strains included in the vaccine.…”
Section: An Evaluation Of Foot-and-mouth Disease Outbreak In Relation Tosupporting
confidence: 90%
“…This was also observed in our findings that animals were vaccinated three months ago. This finding was also coincides with Jamal et al, (2013) who reported very low humoral immune responses against FMDV by the locally produced vaccines. The failure of vaccination may be due to differences between the circulating field strains and the strains included in the vaccine.…”
Section: An Evaluation Of Foot-and-mouth Disease Outbreak In Relation Tosupporting
confidence: 90%
“…A manufacturer may produce a good vaccine but if it is stored poorly then it may not function well when it is used and thus there is a need to determine vaccine quality, at the point of production, and also efficacy during vaccination campaigns. 4 The text above indicates that there are a number of limitations and problems associated with current FMDV vaccines (eg, lack of cross protection, short duration of immunity, lability, requirement for high containment facilities to produce it) and thus there is interest in developing improved vaccines which address at least some of these shortcomings. It may well be that there will not be a single solution to these different issues and indeed the most important features of a vaccine …”
Section: Notesmentioning
confidence: 99%
“…Worldwide, at least two billion FMD vaccinations are applied in China, South America, parts of Asia and the Middle East (Paton et al., ) for routine prophylactic FMD control, but many are not tested to see whether they meet standard potency (≥ 3 PD 50 ) as defined in the OIE Manual of Diagnostic Tests and Vaccines for Terrestrial Animals (the Manual, OIE, ). A recent paper shows that many locally produced FMD vaccines do not meet the minimum OIE potency criteria of 75% protection (Jamal et al., ). In contrast, strategic reserves or antigen banks hold high‐quality, higher potency (≥ 6 PD 50 ) vaccine antigen concentrates (VACs) for emergency formulation to use as a temporary, targeted response measure as an adjunct to movement control and stamping out in countries with OIE status, FMD free country where vaccination is not practised .…”
Section: Vaccination As An Emergency Response Measurementioning
confidence: 99%